Quine - Hylton, Peter (Routledge, 2007)
Quine was one of the foremost philosophers of the Twentieth century. In this outstanding overview of Quine's philosophy, Peter Hylton shows why Quine is so important and how his philosophical naturalism has been so influential within analytic philosophy.